The utility of information collected by occupational disease surveillance systems. (23rd October 2015) - Money, A.; Carder, M.; Hussey, L.; Agius, R. M.
Abstract : Background: The Health and Occupation Research (THOR) network in the UK and the Republic of Ireland (ROI) is an integrated system of surveillance schemes collecting work-related ill-health (WRIH) data since 1989. In addition to providing information about disease incidence, trends in incidence and the identification of new hazards, THOR also operates an ad hoc data enquiry service enabling interested parties to request information about cases of WRIH reported to THOR. Aims: To examine requests for information made to a network of surveillance schemes for WRIH in the UK. Methods: Analysis via SPSS of data requests received by THOR between 2002 and 2014. Results: A total of 631 requests were received by THOR between 2002 and 2014. Requests were predominantly submitted by participating THOR physicians (34%) and the main THOR funder—the UK Health & Safety Executive (HSE) (31%). The majority (67%) of requests were for information about work-related respiratory or skin disease with relatively few requests for other diagnoses, such as musculoskeletal or mental ill-health. Requests frequently related to a specific industry and/or occupation (42%) and/or a specific causal agent (58%). Conclusions: Data collected by occupational disease surveillance systems such as THOR are an extremely useful source of information, the use of which extends beyond informing government on disease incidence and trends in incidence. The data collected provide a framework that can assist a wide range of enquirers with clinical diagnoses, identification of suspected causative agents/exposures and to highlight growing risks in particular industrial and occupational sectors.